Recent advances in nanotechnology - Mahendra Kumar Sahu; Rajni Yadav; Sandeep Prasad Tiwari (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
Introduction: Recent advances in nanotechnology have shown significant progress in various fields. Nanotechnology involves the manipulation and control of matter at the nanoscale, typically ranging from 1 to 100 nanometers. This field has the potential to revolutionize industries such as electronics, medicine, energy, and materials science. Nanotechnology has led to the development of smaller and more efficient devices in electronics. Nanoscale transistors and memory chips have increased computing power and storage capacity. Additionally, nanomaterials like carbon nanotubes and graphene have shown promise in creating flexible and transparent electronics.  Method and materials: In medicine, nanotechnology has opened new possibilities for targeted drug delivery and imaging. Nanoparticles can be designed to specifically target cancer cells, delivering drugs directly to the affected area while minimizing side effects. Nano-sensors can also be used for early detection of diseases and monitoring of patient health. Energy is another area where nanotechnology has made significant advancements. Nanomaterials such as quantum dots and nanowires have improved the efficiency of solar cells, making them more cost-effective and sustainable. Nanotechnology also plays a role in energy storage, with the development of high-capacity batteries and supercapacitors. Materials science has also benefited from nanotechnology. Nanocomposites, which are materials with nanoscale fillers, have enhanced mechanical, thermal, and electrical properties. These materials find applications in the aerospace, automotive, and construction industries.  Conclusion: Overall, recent advances in nanotechnology have paved the way for exciting possibilities in various fields. Continued research and development in this area hold the potential for further breakthroughs and advancements in the future.